2015
DOI: 10.1007/s10995-015-1844-5
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, Physical Activity and Sedentary Behaviors in Children with an Autism Spectrum Disorder

Abstract: These findings suggest that ASD diagnosis is not significantly associated with obesity status after adjustment for possible secondary conditions and medication use. Decision makers, clinicians, and researchers developing interventions for children with ASDs should consider how secondary conditions may impact obesity and related activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
49
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 24 publications
5
49
1
2
Order By: Relevance
“…Although our cohort was small and this could represent a chance finding, it does raise concerns about the risk for obesity in this population, and is consistent with other studies that have identified a higher prevalence of obesity in children with ASD (Chen et al 2010; Corvey et al 2016; Curtin et al 2010; Dreyer Gillette et al 2015). …”
Section: Discussionsupporting
confidence: 89%
“…Although our cohort was small and this could represent a chance finding, it does raise concerns about the risk for obesity in this population, and is consistent with other studies that have identified a higher prevalence of obesity in children with ASD (Chen et al 2010; Corvey et al 2016; Curtin et al 2010; Dreyer Gillette et al 2015). …”
Section: Discussionsupporting
confidence: 89%
“…The elevated obesity prevalence based on nationally representative samples in children with ASD compared with those without the condition has been previously reported by our group 10 and others 9,18,24,25,35 as well as in school-based and clinical samples. 8,[26][27][28]36 Chen et al reported an obesity prevalence of 21.1% among 10-17-year-olds in the 2003 round of NSCH, similar to our estimates, and consistent with a leveling off in prevalence trends over time seen in other nationally representative samples of US children.…”
Section: Discussionsupporting
confidence: 78%
“…Children with ASD often exhibit selective eating, frequently resulting in low intakes of fruits and vegetables with ASD and high intakes of calorically dense foods. [14][15][16][17] As youth age, they are more likely to have access to more energy-dense snacks and less engagement in physical activity compared with the peers without ASD, 18 and their physical activity levels decline with age. 19,20 Parents of children with ASD report using television for its calming effect, 21 which may contribute to high levels of sedentary behavior.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen studies were published between 2010 and 2016 9,2437 . Four studies were case-control 24,27,31,33 and eleven studies were cross-section 9,25,26,28–30,32,3437 . The studies encompassed a total of 49,937,078 participants and 1,045,538 individuals with ASD.…”
Section: Resultsmentioning
confidence: 99%